2011
DOI: 10.1002/dc.21684
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of S100P, mesothelin, fascin, prostate stem cell antigen, and 14‐3‐3 sigma in diagnosing pancreatic adenocarcinoma in cytological specimens obtained by endoscopic ultrasound guided fine‐needle aspiration

Abstract: Endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) of the pancreas is an efficient and minimally invasive procedure for the diagnosis and staging of pancreatic adenocarcinoma. Because of some limitations of EUS-FNA in diagnosis of well-differentiated or early stage cancers, the purpose of this study is to assess the added benefit of immunohistochemistry. We studied five proteins overexpressed in pancreatic adenocarcinoma, namely, prostate stem cell antigen, fascin, 14-3-3 sigma, mesothelin and S100P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 25 publications
(44 reference statements)
0
31
0
Order By: Relevance
“…In addition, a previous study revealed that TRB3 disrupts insulin signal by binding directly to Akt and blocking PKB/AKT activation (8). Recently, it was demonstrated that salinomycin stimulated endoplasmic reticulum stress and mediated autophagy via the ATF4-CHOP-TRIB3-AKT1-mammalian target of rapamycin cascades in human non-small-cell lung cancer cells (21).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a previous study revealed that TRB3 disrupts insulin signal by binding directly to Akt and blocking PKB/AKT activation (8). Recently, it was demonstrated that salinomycin stimulated endoplasmic reticulum stress and mediated autophagy via the ATF4-CHOP-TRIB3-AKT1-mammalian target of rapamycin cascades in human non-small-cell lung cancer cells (21).…”
Section: Discussionmentioning
confidence: 99%
“…The results of that study demonstrate that PVHL, mapsin, S100P and IMP-3 constitute the most effective panel of markers in the distinction of pancreatic adenocarcinoma from benign/reactive pancreatic ducts. Another study [43] on EUS-FNAB in cases of pancreatic adenocarcinoma demonstrates that among five antibodies, S100P reveals the best diagnostic characters showing 90% of sensitivity and 67% of specificity. Fascin shows high specificity (92%) but low sensitivity (38%).…”
Section: Reviewmentioning
confidence: 99%
“…Its overexpression has been observed in more than 90% of pancreatic ductal adenocarcinomas, [162][163][164][165][166][167] 76% of gallbladder adenocarcinomas, 168 and 76% to 92% of adenocarcinomas of extrahepatic bile ducts. 165,169,170 Interestingly, the frequency of S100P overexpression is much lower in intrahepatic cholangiocarcinomas, seen in only 27% in one study 167 and 48% in another study.…”
Section: Immunomarkers To Distinguish Pancreaticobiliary Adenocarcinomentioning
confidence: 99%